Effect of the Modification of p24 Peptide Antigen on Dendritic Cell Uptake and T Cell Activation - L. Smith, Peter; J. Norgate, Kirstie; Hegarty, Eve; Gregeda, Nathalie; Heelas, Edward; Sommerfelt, Maja; Lange, Tonnes; Hovden, Arnt-Ove; Sorenson, Birger; G. Dalgleish, Angus; Bodman-Smith, Mark (Current HIV Research, 2017)
Background: Vacc-4x is a candidate therapeutic vaccine consisting of 4 modified peptides based on conserved regions of HIV-1 p24Gag. Vacc4x has been shown to induce long term cellular immunity in immunized infected individuals resulting a reduction in viral load on treatment interruption. Objective: Vacc-4x peptides are modified. In this study the effect of modification on uptake of the peptides into PBMC, their subsequent presentation and antigenicity was tested. The feasibility of using an in vitro culture system for testing immunogenicity of peptides using PBMC from uninfected donors was also assessed. Methods: Labelled peptides were evaluated for uptake into PBMC using flow cytometry or confocal microscopy. Monocyte derived dendritic cells (DC) and autologous T cells were co-cultured with native and modified peptide antigens derived from p24. Activation was measured by flow cytometry and IFN-γ ELISPOT. Results: Peptide modifications significantly increased peptide uptake by monocyte derived dendritic cells. Both the native (unmodified) and Vacc-4x (modified) peptide loaded DC could activate CD4+ and CD8+ T cell responses in vitro. Individual modified peptides induced greater responses than their native counterparts. The grouped Vacc-4x peptides elicited greater IFN γ responses than their native grouped counterparts at a lower concentration, however this effect was not detected at higher concentrations. Conclusion: These data indicate that the modifications increase uptake, alter the antigenicity of HIV- 1 p24 Vacc-4x peptides and increase the breadth of the response to the Vacc-4x peptides. The in vitro cell culture system is a suitable model for the antigenic assessment of peptide antigens.
Keywords: T cell